Forest management as political practice: Indian experiences with the accommodation of multiple interests - Baviskar, A. (2001)
The multiplicity of interests around forests in India reflects the range of social groups who have a stake in their management. Forestry practices, and the ideologies that legitimize them, have been shaped by the political differences prevailing among these collectivities. This paper examines how power relations intersecting the global, national and local levels affect forest management. It attempts to link the articulation and accommodation of specific interests in forestry to the configurations of power obtaining in particular social and historical circumstances. The analysis focuses on the central role of state institutions and ideologies in shaping forest management and discusses how state practices have changed in response to pressures from global and local actors. In conclusion, the paper examines the potential within contemporary forest management practices to further the objectives of social justice and ecological sustainability.